A prospective observational study of role of pedis scoring in predicting complications of diabetic foot in a tertiary centre - Sivakumar, Sivaranjani; Kesavan, Rajesh; Reddy , Balachandar Kariappa (International Surgery Journal, 2023)
Background: Diabetes mellitus is one of the most common non-communicable diseases affecting major population in the world. Diabetic foot ulcer still remains the most common manifestation of diabetes mellitus requiring hospitalisation and invariably resulting in increased risk of morbidity. Our aim is to know the usefulness of PEDIS scoring in identifying the severity of diabetic foot ulcer and its management. Methods: In this prospective observational study, data of patients with foot ulcer who came to Apollo hospital in Chennai were collected for one year from July 2021 to May 2022. They were followed up for a period of six months. Patients were assessed and classified according to the PEDIS scoring system. All the data were analyzed by IBM SPSS statistics for windows version 25.0 (IBM corp, Armonk, Newyork USA). All p values <0.05 were considered as statistically significant. Results: Out of one seventy-five patients, one hundred and thirteen were categorized as low risk group with a score between 0-7 and sixty-two as high-risk group with a score between 8-12. Majority of the high-risk groups developed complications like non healing ulcer, osteomyelitis, amputation. It is more prevalent among men with age preponderance for elderly. Whereas management of low-risk groups were limited only to conservative management and debridement. Of twenty-one patients with osteomyelitis, thirteen patients underwent amputation. Conclusions: Based on our study, we have come to a conclusion that the PEDIS scoring system actually helps in grading the diabetic foot and its management.